Does childhood anxiety evoke maternal control? A genetically informed study. - Eley, T; Napolitano, M; Lau, J; Gregory, A (2010)
BACKGROUND: Despite theoretical and empirical support for an association between maternal control and child anxiety, few studies have examined the origins of this association. Furthermore, none use observer-ratings of maternal control within a genetically informative design. This study addressed three questions: 1) do children who experience maternal control report higher anxiety levels than those who do not?; 2) to what extent do genetic and environmental factors influence maternal control and child anxiety?; 3) to what extent do genetic and environmental factors influence the associations between child anxiety and maternal control? METHOD: Five hundred and thirty 8-year-old children (from 265 twin pairs) and their mothers were observed participating in an 'etch-a-sketch' task from which maternal control was rated. Children rated their anxiety using the Screen for Child Anxiety Related Emotional Disorders. RESULTS: Children who experienced maternal behaviour rated as 'extreme control' reported higher anxiety levels than those who did not. Maternal control was highly heritable (A = .63), high self-rated anxiety less so (h(2)(g) = .36). The overlap between high child anxiety and maternal control was primarily due to shared genetic factors. CONCLUSIONS: These results suggest that maternal control is likely to have been elicited by children with high levels of anxiety.